Microvascular Resistance Predicts Myocardial Salvage and Infarct Characteristics in ST‐Elevation Myocardial Infarction - Payne, Alexander R. (Blackwell Publishing Ltd, 2012)
BACKGROUND: The pathophysiology of myocardial injury and repair in patients with ST‐elevation myocardial infarction is incompletely understood. We investigated the relationships among culprit artery microvascular resistance, myocardial salvage, and ventricular function. METHODS AND RESULTS: The index of microvascular resistance (IMR) was measured by means of a pressure‐ and temperature‐sensitive coronary guidewire in 108 patients with ST‐elevation myocardial infarction (83% male) at the end of primary percutaneous coronary intervention. Paired cardiac MRI (cardiac magnetic resonance) scans were performed early (2 days; n=108) and late (3 months; n=96) after myocardial infarction. T(2)‐weighted‐ and late gadolinium–enhanced cardiac magnetic resonance delineated the ischemic area at risk and infarct size, respectively. Myocardial salvage was calculated by subtracting infarct size from area at risk. Univariable and multivariable models were constructed to determine the impact of IMR on cardiac magnetic resonance–derived surrogate outcomes. The median (interquartile range) IMR was 28 (17–42) mm Hg/s. The median (interquartile range) area at risk was 32% (24%–41%) of left ventricular mass, and the myocardial salvage index was 21% (11%–43%). IMR was a significant multivariable predictor of early myocardial salvage, with a multiplicative effect of 0.87 (95% confidence interval 0.82 to 0.92) per 20% increase in IMR; P<0.001. In patients with anterior myocardial infarction, IMR was a multivariable predictor of early and late myocardial salvage, with multiplicative effects of 0.82 (95% confidence interval 0.75 to 0.90; P<0.001) and 0.92 (95% confidence interval 0.88 to 0.96; P<0.001), respectively. IMR also predicted the presence and extent of microvascular obstruction and myocardial hemorrhage. CONCLUSION: Microvascular resistance measured during primary percutaneous coronary intervention significantly predicts myocardial salvage, infarct characteristics, and left ventricular ejection fraction in patients with ST‐elevation myocardial infarction. (J Am Heart Assoc. 2012;1:e002246 doi: 10.1161/JAHA.112.002246)